Implementation of the Fisher-Yates Shuffle Algorithm in Exam-Problem Randomization on M-Learning Applications - Chandra Kirana; Benny Wijaya; Abdul Holil (Department of Informatics, Universitas Muhammadiyah Surakarta, Indonesia, 2021)
Many schools are currently using conventional approaches in learning material deliveries and examination methods. Conventional examination processes referred to here are the provision of question sheets in paper form. They have several drawbacks, such as students cheating and a waste of paper printing costs. To overcome these problems, we propose an online examination system. The online system leaves students to work on a different question set from other students. The feature is made possible by applying a randomization algorithm. There are several algorithms for scrambling questions, one of which is the Fisher-Yates Shuffle algorithm. This study aims to ease schools in the implementation of quality exams that may find out the level of student understanding of study materials and reduce the risk of cheating. The research product works on Android smartphones, which may be attractive to students and schools. The product allows schools to hold quality exams and reduce paper costs.